Bolse vita - Fekete, Ibolya (Hungary, 1996)
Set in Central Europe following the fall of Communism in 1989, this German-Hungarian ensemble piece centers on the reactions and attempts to get by in a brand new environment. Yura and Vadim are Russian musicians trying to get to Belgrade for a performance. Impoverished Sergei is trying to get there too. He sells knives to earn the money he needs. British Maggie and American Susan have drifted to Hungary in search of excitement. All five characters accidentally collide in the Bolse Vita bar in Budapest. While Sergei continues selling his cutlery in the open-air market, Yura and Maggie begin an affair as do Susan and Vadim. Much of the story chronicles the short-lived euphoria that followed the demise of oppression, but unfortunately, the people's happiness abruptly ended when the realities of life set in. So it goes for the characters as they all begin drifting towards their disparate destinies.